Increased adhesion of Escherichia coli to mucosal cells from infants with protracted diarrhoea: a possible factor in the pathogenesis of bacterial overgrowth and diarrhoea. Issue 6 (June 1983) - Candy, D C; Leung, T S; Marshall, W C; Harries, J T
Abstract : Mucosal adhesion of bacteria has been studied in eight infants with protracted diarrhoea and malnutrition, using a buccal epithelial cell technique. A known non-adhesive strain of Escherichia coli (O1:K1:H7) adhered to a significantly greater (p less than 0.001) proportion of buccal epithelial cells from patients with protracted diarrhoea, compared with children with acute diarrhoea, healthy infants, and healthy adults. Also, Enterobacteria isolated from the jejunum or stools of patients with protracted diarrhoea adhered to far greater numbers of their own buccal epithelial cells compared with healthy adults. These results suggest that bacterial adhesion may play an important role in the pathogenesis of protracted diarrhoea.